Nat Geo amazing! 100 people, places, and things that will wow you - Bellows, Melina Gerosa (Washington, D.C. National Geographic Society, 2010)
Presents a hundred curiosities from the pages of "National Geographic" and its related television programs, including wonders from nature and science, notable facts from history, the ways of different cultures, and daring adventures.
Keywords: Curiosities and wonders; Natural history -- Miscellanea